Effect Of Copper And Zinc Toxicity On Physiological And Biochemical Parameters In Vigna Mungo (L.) Hepper - RAJESH DHANKHAR; RADHA SOLANKI (International Journal of Pharma and Bio Sciences, 2011)
The present study aimed at investigating the effects of copper and zinc in Vigna mungo (L.) growth and metabolism. Physiological parameters decrease consequently with increasing copper and zinc concentration in nutrient medium. Copper at 0.2mM concentration led to 32.12% and 47.82% reduction in fresh weight and dry weight respectively whereas, zinc at 1.50mM concentration resulted in 23.83% and 70.56% decrease in fresh weight and dry weight of seedlings with respect to control. The combined effect of copper and zinc on seedling growth was antagonistic at low concentration but showed additive effect at high concentrations. The results demonstrated an increase in DNA content/mg fr. Wt. of seedlings up to 124.45% at 0.2mM Cu + 1.50mM Zn and RNA content was adversely affected in all treatment conditions. Moreover, seedlings exposed to copper and zinc metal ions have shown significant variations in phosphate hydrolysis and mobilization from source to sink and specific activity of acid phosphatase.